Diversity of Insect Types in New Rice Fields - Rahmawasiah, Rahmawasiah; Arnama, I Nyoman (Agro Bali : Agricultural Journal, 2025)
Insects as a component of the rice field ecosystem have an important role in the food web, namely as herbivores, carnivores (predators and parasitoids) and detritivores. This research aims to examine insect diversity in new rice fields. The research was carried out by taking insect samples using yellow traps, farm cops, pitfalls and light traps. The collected insects are then identified in the laboratory. The research results showed that 28 species of insects were obtained using the yellow trap, 34 species of farmcop, five species of pitfall and seven species of light trap. The composition of insects based on their role is 49% herbivores, 29% natural enemies (22% predators and 7% parasitoids), and 22% other insects. Insect diversity index 3.28 with evenness 0.91. The insects found in the new rice fields are 9 orders, 32 families, 41 species and 1317 individuals consisting of herbivores, natural enemies and other insects.  Insect diversity is relatively high, with an even distribution of species. The results obtained can be used for pest management in rice plantations.